Regulation of dendritic spines in the amygdala following sleep deprivation - Rexrode, Lindsay; Tennin, Matthew; Babu, Jobin; Young, Caleb; Bollavarapu, Ratna; Lawson, Lamiorkor Ameley; Valeri, Jake; Pantazopoulos, Harry; Gisabella, Barbara (Frontiers in Sleep, 2023)
The amygdala is a hub of emotional circuits involved in the regulation of cognitive and emotional behaviors and its critically involved in emotional reactivity, stress regulation, and fear memory. Growing evidence suggests that the amygdala plays a key role in the consolidation of emotional memories during sleep. Neuroimaging studies demonstrated that the amygdala is selectively and highly activated during rapid eye movement sleep (REM) and sleep deprivation induces emotional instability and dysregulation of the emotional learning process. Regulation of dendritic spines during sleep represents a morphological correlate of memory consolidation. Several studies indicate that dendritic spines are remodeled during sleep, with evidence for broad synaptic downscaling and selective synaptic upscaling in several cortical areas and the hippocampus. Currently, there is a lack of information regarding the regulation of dendritic spines in the amygdala during sleep. In the present work, we investigated the effect of five hours of sleep deprivation on dendritic spines in the mouse amygdala. Our data demonstrate that sleep deprivation results in differential dendritic spine changes depending on both the amygdala subregions and the morphological subtypes of dendritic spines. We observed decreased density of mushroom spines in the basolateral amygdala of sleep-deprived mice, together with increased neck length and decreased surface area and volume. In contrast, we observed greater densities of thin and stubby spines in sleep-deprived mice in the lateral and central amygdala, indicating that downscaling selectively occurs in these two spine types. Greater neck diameters for thin spines in the lateral and basolateral nuclei of sleep-deprived mice provide further support for spine type-selective synaptic downscaling in these areas during sleep. Our findings suggest that sleep promotes synaptic upscaling of mushroom spines in the basolateral amygdala, and downscaling of selective spine types in the lateral and central amygdala. In addition, we observed decreased density of phosphorylated cofilin immunoreactive and growth hormone immunoreactive cells in the amygdala of sleep-deprived mice, providing further support for upscaling of dendritic spines during sleep. Overall, our findings point to region- and spine-type-specific changes in dendritic spines during sleep in the amygdala, which may contribute to consolidation of emotional memories during sleep.